Multiple voices in WWII exhibitions: three studies at the National Museum of Singapore (2015-2020) - Ng, Sor Luan (Nanyang Technological University, 2022)
This thesis begins by investigating if objectivity can occur in museums and exhibitions and proposes polyvocality for achieving a fairer representation. It proceeds to examine if and how polyvocality is employed in the narrative of war history in museums and exhibitions through investigating three on-going or recent war exhibitions between 2015-2020 in Singapore; Syonan-To at the Singapore History Gallery in the National Museum of Singapore (NMS), the Survivng Syonan (1942-1945) Life in Singapore Galleries in NMS, and the Witness to War: Remembering 1942 exhibition at the same museum. This study collects background information on NMS and the exhibitions. Field studies were conducted at Syonan-To and Surviving Syonan (1942-1945) while data on Witness to War: Remembering 1942 were collected from various sources. The representations in war exhibitions at NMS is affected by the national identity building role of NMS, the space and the collections available. NMS has consistently worked to increase its collection and experimented with new ways of exhibiting thus allowing for better polyvocality in its war representations. Its collaboration with overseas museums and institutions has also helped increase the range of war stories it can tell. Going forward, NMS could increase such collaborative projects, experiment with different story-telling techniques and work to address the lack of representations of communities and events in WWII narratives in Singapore.